2016
DOI: 10.1002/jctb.4918
|View full text |Cite
|
Sign up to set email alerts
|

A review of biomass energy – shortcomings and concerns

Abstract: Biomass has been, historically, the main source of global energy, primarily for cooking, heating, and small cottage industries. It is witnessing a strong revival and is currently used in a multitude of applications. It provides between 10 and 14% of world energy, with the potential to provide 30-40 + % and is an integral component of all energy scenarios. Biomass energy is providing multiple energy, environmental, and socio-economic benefits, both modern and traditional, ranging from electricity, heat, to tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 34 publications
0
51
0
4
Order By: Relevance
“…Although it is possible to have a direct competition between food and fuel (food versus fuel), in most cases a symbiosis is hitherto the norm (food and fuel) (Rosillo‐Calle & Johnson, ; Kline et al ., ; Rosillo‐Calle, ). Potential conflicts can also be reduced and even avoided by sustainability policies and market regulation when land availability is considered to be a limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible to have a direct competition between food and fuel (food versus fuel), in most cases a symbiosis is hitherto the norm (food and fuel) (Rosillo‐Calle & Johnson, ; Kline et al ., ; Rosillo‐Calle, ). Potential conflicts can also be reduced and even avoided by sustainability policies and market regulation when land availability is considered to be a limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a wide range of gas, liquid, and solid fuel options are possible by HTL, depending on the fuel market conditions [10]. HTL has the flexibility for processing various categories of biomass feedstock such as wastes, aquatic, lignocellulosic, herbaceous, food processing wastes, fungus [8,14], cyanobacteria as well as the biochemical wastes resulted from macro and microorganisms [7,[14][15][16][17][18][19][20][21]. This review focuses on microalgal feedstock, despite diverse HTL feedstocks beeing reported in the literature [14,[22][23][24][25].…”
Section: Potential and Availability Of Microalgae As Energy Sourcementioning
confidence: 99%
“…While the former takes place in million years, the latter takes only minutes in the laboratory [26]. In addition, using microalgae as a source for biocrude may reduce greenhouse gas emissions for a safer environment [11,20,[27][28][29][30][31][32]].…”
Section: Potential and Availability Of Microalgae As Energy Sourcementioning
confidence: 99%
“…First generation bioethanol, such as that produced from corn in the USA and sugarcane ethanol in Brazil, is now widely produced and used, and currently is the liquid biofuel with the highest production volume (> 90 GL) . Bioethanol can be readily used in current supply chains, with 86% of cars sold in Brazil in 2008 capable of using ethanol or a mixture of ethanol and fossil fuel petroleum .…”
Section: Biofuels Productionmentioning
confidence: 99%